2013
DOI: 10.1016/j.cognition.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

What counts in grammatical number agreement?

Abstract: Both notional and grammatical number affect agreement during language production. To explore their workings, we investigated how semantic integration, a type of conceptual relatedness, produces variations in agreement (Solomon & Pearlmutter, 2004). These agreement variations are open to competing notional and lexical-grammatical number accounts. The notional hypothesis is that changes in number agreement reflect differences in referential coherence: More coherence yields more singularity. The lexical-grammatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
67
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 53 publications
8
67
4
1
Order By: Relevance
“…This conception of number markedness has been supported by a range of findings from error rates and reaction times in production (e.g., Bock & Miller, 1991;Brehm & Bock, 2013;Eberhard, 1997;Staub, 2009), as well as from computational modeling (Eberhard et al, 2005). Relevant to the present study, Eberhard (1997) showed in a language production task that plural nouns embedded within a larger singular NP (e.g., The key to the cabinets .…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…This conception of number markedness has been supported by a range of findings from error rates and reaction times in production (e.g., Bock & Miller, 1991;Brehm & Bock, 2013;Eberhard, 1997;Staub, 2009), as well as from computational modeling (Eberhard et al, 2005). Relevant to the present study, Eberhard (1997) showed in a language production task that plural nouns embedded within a larger singular NP (e.g., The key to the cabinets .…”
mentioning
confidence: 49%
“…For example, the production of well-formed sentences in English requires speakers to compute dependencies between discontinuous elements (e.g., a subject noun phrase [NP] and verb), sometimes at a great distance. Behavioral psycholinguistic research from speech production has repeatedly shown that this process can be error-prone (e.g., Bock & Miller, 1991;Brehm & Bock, 2013;Staub, 2009). Importantly, this line of research has also shown that examining the factors that influence error rates can provide a clear window into the cognitive mechanisms supporting the computation of grammatical relations, as well as identify the range and role of linguistic cues that influence how we compute agreement and discontinuous dependencies in language more generally.…”
mentioning
confidence: 99%
“…Staub (2009) argued that these findings supported the notion that the ambiguously-valued global number representation (e.g., a ‘slightly plural’ S(r) value) gives rise to uncertainty about the correct verb form, which in turn leads to longer RTs. Thus, in addition to accurately predicting effects on attraction rates of notional number (e.g., Bock, Carreiras, & Meseguer, 2012; Brehm & Bock, 2013), morphological richness (e.g., Foote & Bock, 2012; Lorimor, Bock, Zalkind, Sheyman, & Beard, 2008), and other factors (see Bock & Middleton, 2011, for a recent review), the MM model also correctly predicts symmetrical attraction effects during language production.…”
Section: Introductionmentioning
confidence: 91%
“…In the RT data provided by Staub (2009), the globally ambiguous number representation of the subject NP symmetrically impacted both correct and incorrect decisions about verb number during a forced choice task (see also Brehm & Bock, 2013; Haskell & MacDonald, 2003). Extending this logic to comprehension, this would predict that plural attractors embedded in PP modifiers should cause symmetrical interference, affecting the processing of both grammatical and ungrammatical verbs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation